Impact of Bi3+ heterovalent doping in organic-inorganic metal halide perovskite crystals - Nayak, Pabitra K.; Sendner, Michael; Lovrinčić, Robert; Pucci, Annemarie (Journal of the American Chemical Society, 2018)
Intrinsic organic-inorganic metal halide perovskites (OIHP) based semiconductors have shown wide applications in optoelectronic devices. There have been several attempts to incorporate heterovalent metal (e.g., Bi3+) ions in the perovskites in an attempt to induce electronic doping and increase the charge carrier density in the semiconductor. It has been reported that inclusion of Bi3+ decreases the band gap of the material considerably. However, contrary to the earlier conclusions, despite a clear change in the appearance of the crystal as observed by eye, here we show that the band gap of MAPbBr3 crystals does not change due the presence of Bi3+ in the growth solution. An increased density of states in the band gap and use of very thick samples for transmission measurements, erroneously give the impression of a band gap shift. These sub band gap states also act as nonradiative recombination centers in the crystals.